2019
DOI: 10.3899/jrheum.180946
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Nonadherence with Hydroxychloroquine Therapy in Systemic Lupus Erythematosus

Abstract: Objective.Hydroxychloroquine (HCQ) is a cornerstone to managing systemic lupus erythematosus (SLE), yet adherence to medication is poor. We sought to measure the association of adherence with 5 “dimensions of adherence” as articulated by the World Health Organization for chronic conditions: the patient’s socioeconomic status, and patient-, condition-, therapy-, and healthcare system–related factors. Our longterm goal is to generate evidence to design effective interventions to increase adherence.Methods.The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
(34 reference statements)
4
20
0
Order By: Relevance
“…1 Their study adds to the number of papers stressing the correlation of low HCQ blood level and increased risk of disease exacerbation, due mainly to lack of treatment adherence. [2][3][4] The paper is in agreement with other clinical studies showing that blood HCQ concentration above 500 ng mL -1 improves clinical activity of SLE. 2 In vitro studies have demonstrated that, at such concentrations, HCQ inhibits MHC-class II antigen presentation and Toll-like receptor 9 (TLR9) signaling in response to DNA containing CpG motifs, 5 an important pathway in the production of type-1 interferons thought to play a role in the pathogenesis of SLE.…”
Section: Letter To the Editorsupporting
confidence: 90%
See 1 more Smart Citation
“…1 Their study adds to the number of papers stressing the correlation of low HCQ blood level and increased risk of disease exacerbation, due mainly to lack of treatment adherence. [2][3][4] The paper is in agreement with other clinical studies showing that blood HCQ concentration above 500 ng mL -1 improves clinical activity of SLE. 2 In vitro studies have demonstrated that, at such concentrations, HCQ inhibits MHC-class II antigen presentation and Toll-like receptor 9 (TLR9) signaling in response to DNA containing CpG motifs, 5 an important pathway in the production of type-1 interferons thought to play a role in the pathogenesis of SLE.…”
Section: Letter To the Editorsupporting
confidence: 90%
“…1 Their study adds to the number of papers stressing the correlation of low HCQ blood level and increased risk of disease exacerbation, due mainly to lack of treatment adherence. 24…”
mentioning
confidence: 99%
“…Adherence to HCQ therapy in patients with rheumatic diseases, including RA, is generally low (51,52). It has been reported that adherence may be further lowered due to perceived concerns surrounding its adverse cardiovascular effect in patients with COVID‐19 (9).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, multiple studies have shown high levels of very poor adherence, generally ranging from 20% to 50% of patients 38,39,40,41,42 . Common reasons for poor adherence cited by patients include fear of adverse effects and lack of understanding of the benefits 32,43 .…”
Section: Rheumatologymentioning
confidence: 99%